2013
DOI: 10.1097/sle.0b013e31828e389d
|View full text |Cite
|
Sign up to set email alerts
|

2 L PEG Plus Ascorbic Acid Versus 4 L PEG Plus Simethicon for Colonoscopy Preparation

Abstract: According to our data, low-volume PEG+Asc has comparable efficacy, safety, and tolerability as high-volume PEG+Sim; therefore, it can be considered as a good alternative solution for bowel preparation. More improvements are necessary to achieve the target of a perfect preparation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 30 publications
0
29
1
Order By: Relevance
“…Twenty-one trials included analyzable bowelcleanliness outcomes (64)(65)(66)(67)(68)(69)(70)(71)(72)(74)(75)(76)79,(81)(82)(83)(84)(85)(86)88,89 ). High-volume PEG-ELS did not show a signifi cant increase in bowel cleanliness (OR, 1.03; 95% CI, 0.80-1.32).…”
Section: Polyethylene Glycol-electrolyte Lavage Solutionmentioning
confidence: 89%
See 1 more Smart Citation
“…Twenty-one trials included analyzable bowelcleanliness outcomes (64)(65)(66)(67)(68)(69)(70)(71)(72)(74)(75)(76)79,(81)(82)(83)(84)(85)(86)88,89 ). High-volume PEG-ELS did not show a signifi cant increase in bowel cleanliness (OR, 1.03; 95% CI, 0.80-1.32).…”
Section: Polyethylene Glycol-electrolyte Lavage Solutionmentioning
confidence: 89%
“…In trials of high-volume PEG-ELS (≥3 l) compared with lowvolume PEG-ELS (<3 l), willingness to repeat bowel cleansing regimen was lower in the high-volume group (OR, 0.34; 95% CI, 0.18-0.64) ( 63,66,69,70,78,79,81,83,85 ) and higher for the split-dose group (OR, 1.76; 95% CI, 1.06-2.91; P =.03) ( 39 ). For OSS, willingness to repeat was not reported in any of the studies ( 92,93 ) .…”
Section: Peg-3350 Powdermentioning
confidence: 95%
“…In recent studies PEGþAsc was shown to be as tolerable 41 or more tolerable 42 than 4 L PEG preparations. Similarly, when compared with other PEG-based preparations such as 4 L PEG þ simethicone 43,44 , or 2 L PEG þ citrate þ simethicone with bisacodyl 45 , PEGþAsc had comparable acceptability and tolerability. In our study, we confirm a high acceptability for PEGþAsc, similar to the NaP group which is an essential element to ensure high population adherence within screening programs.…”
Section: Discussionmentioning
confidence: 69%
“…Two RCTs reported that willingness to repeat bowel preparation was higher with the low-volume formulation than with the 4-L PEG (73% vs 65%, P = 0.079) [29,30] . In another randomized study comparing PEG-A to 4-L PEG plus simethicone, no differences were observed in efficacy, safety or tolerance [33] . In a RCT that compared PEG-A to another new low-volume solution (PEG-citrate-simethicone), both in combination with bisacodyl [34] , the latter preparation was more effective in bowel cleansing for outpatient colonoscopy.…”
Section: Resultsmentioning
confidence: 99%
“…A study compared the quality of cleansing with patient tolerance of 2 L of PEG-ELS, ad-Parra-Blanco A et al . Best preparation for colonoscopy [29] PEG 4 L vs PEG 2 L + ascorbate 72/72 Residual stool score significantly lower with PEG 4 L Corporaal et al [30] PEG 4 L vs PEG 2 L + ascorbate 149/158 PEG + ascorbate less effective in right colon cleansing Marmo et al [31] PEG 4 L vs PEG 2 L + ascorbate 435/433 PEG + ascorbate as effective as high-volume PEG-electrolyte solution but has superior palatability Ell et al [32] PEG 4 L vs PEG 2 L + ascorbate 153/155 PEG + ascorbate same efficacy and safety, better tolerance Gentile et al [33] PEG 4 L vs PEG 2 L + ascorbate 60/60 Similar efficacy Repici et al [34] PEG 2 L + ascorbate vs PEG 2 L + citrate + bisacodyl 202/203 PEG 2 L + citrate + bisacodyl more effective for bowel cleansing Bitoun et al [35] PEG 2 L + ascorbate vs NaP 169/171 PEG + ascorbate at least as efficacious as NaP, comparable efficacy, better tolerability profile Rex et al [22] 4 L PEG SF-ELS vs NaP 68/68 NaP superior bowel cleansing, similar tolerability Renaut et al [37] MC-SP vs NaP 32/41 MC-SP better tolerated, similar cleansing effectiveness Choi et al [38] NaP vs magnesium citrate + NaP (45 mL) 79/80 Both similar effectiveness Schmidt et al [39] MC-SP vs NaP 182/190 MC-SP better tolerance, similar cleansing effectiveness Hookey et al [40] MC-SP + bisacodyl vs MC-SP vs NaP 105/109/101 MC-SP + bisacodyl better colon cleansing in the right colon compared with two other groups Tjandra et al [42] MC-SP vs NaP 120/102 NaP better cleansing Katz et al [41] MC-SP vs PEG 2 L + 10 mg bisacodyl tablets 300/303 Similar quality of cleansing Rex et al [43] PEG 2 L + bisacodyl 5 ministered either on the same day or in a split dose fashion [56,57] . There was no difference in quality (with adequate bowel prep in > 90% patients in both groups).…”
Section: A Key Factor For Optimal Preparation: Timing Of Administrationmentioning
confidence: 99%